Basic and Clinical Understanding of Microcirculation - Fatima Shad, Kaneez; Soheil Saeedi Saravi, Seyed; Luqman Bilgrami, Nazar (IntechOpen, 2020)
Microcirculation is key to providing enough nutrition and oxygen from head to toe. This is possible only through an extensive network of blood vessels spread around the body. Effect of microcirculation abnormalities stretch beyond one's comprehension. The effects could be felt at any age, from the foetal life to the adulthood. The chapters present in this book describe how these abnormalities could lead to diseases such as atherosclerosis, thrombosis, diabetes, hypertension. Disorders of microcirculation could be related to the structural and/or functional damage to the inner lining of the blood vessels. Early identification of these disorders could benefit many ailments including cardiovascular and cerebrovascular diseases such as heart attack and stroke.